Ad hoc mobile wireless networks : principles, protocols, and applications - Sarkar, Subir Kumar (CRC Press, 2013)
"Communication between various devices makes it possible to provide unique and innovative services. Although this inter-device communication is a very powerful mechanism, it is also a complex and clumsy mechanism, leading to a lot of complexity in the present day systems. This not only makes networking difficult but limits its flexibility as well. Many standards exist today for connecting various devices. At the same time, every device has to support more than one standard to make it inter-operable between different devices. Take the example of setting up a network in offices. Right now, entire office buildings have to make provisions for lengths of cable that stretch kilometers through conduits in the walls, floors and ceilings to workers' desks. In the last few years, many wireless connectivity standards and technologies have emerged. These technologies enable users to connect a wide range of computing and telecommunications devices easily and simply, without the need to buy, carry, or connect cables. These technologies deliver opportunities for rapid ad hoc connections, and the possibility of automatic, unconscious, connections between devices. They will virtually eliminate the need to purchase additional or proprietary cabling to connect individual devices, thus creating the possibility of using mobile data in a variety of applications. Wired local area networks (LANs) have been very successful in the last few years and now with the help of these wireless connectivity technologies, wireless LANs (WLANs) have started emerging as a much more powerful and flexible alternatives to the wired LANs"--